Job demands, job resources and innovative work behaviour: a European Union study - Dediu, Vlad; Leka, Stavroula; Jain, Aditya Kailash (Taylor & Francis, 2018)
This study aims to investigate the relationship between several job design variables and innovative work behaviour (IWB). Guided by the Job Demands Resources model, the aim was to evaluate the relationship between work demands (time constraints), resources (autonomy and social support), and other work factors (task monotony, complexity, and dealing with unforeseen circumstances) with idea generation and idea implementation behaviours in a sample of 12,924 participants from the 27 European Union member states in 2010. We also wished to investigate if individual IWB, at the country level, is associated with country innovative performance (an aggregate of process/product and marketing/organizational innovation). We employed a multilevel generalized structural equation model to test our hypotheses. In our final model autonomy, manager encouragement and dealing with unforeseen problems showed the highest positive relationship with idea generation and idea implementation. Conversely, monotonous tasks and working at high speed were negatively related to IWB. Furthermore, we have found strong indications that country-level IWB positively relates to the odds of a country scoring higher on the aforementioned innovation indicators. Between-country unexplained variance in IWB was reduced from 17.1% in our initial model, to 1.9% in our final iteration. Limitations, implications and suggestions for future research are discussed.